THE CONCEPT OF THE POSITION OF REVELATION AS AN ONTOLOGY OF PROPHETIC BASED LEGAL SCIENCE - Romi Saputra; Khudzaifah Dimyati; Absori Absori; Kelik Wardiono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This article aims to answer the position of revelation as a prophetic-based ontology of legal science. If the West issues revelations in science and more specifically in the formation of positive law, and glorifies human reason more, then this article explains that these revelations are part of positive law without ignoring human potential, and placing human potential proportionally. By using philosophical methods and approaches, this article shows that revelation in the study of prophetic law occupies a very high position, revelation functions to provide direction and guidance for reason in understanding reality and the formation of positive law. Law is interpreted by the will of Allah SWT which is based on the Koran and the Sunnah of the Prophet Muhammad. Revelation functions as a guide containing norms, values and rules, while reason is tasked with finding laws based on revelation's direction. For this reason, revelation, reason and the senses never come into conflict between the two, instead they become one unit, mutually reinforcing and reinforcing each other. The combination of revelation with reason and human life is then known as the Islamic moderation paradigm which synergizes things that are permanent with things that are flexible, combines the understanding of the Salaf with contemporary reforms (tajdid), is not jumud and liberal, and understand Islam comprehensively. Conflict between revelation and reason will only occur if one of them is fixed and the other is flexible, then of course the fixed one is superior to the flexible one, or both are equally flexible, so even if one is determined by interpreting the view of reason.